Personal injury and wrongful death damages calculations transatlantic dialogue - Thornton, Robert; Ward, John O. (Contemporary studies in economic and financial analysis ;, 2009)
The volume focuses on litigation damages, economic and non-economic, including punitive damages; their definitions, calculations, and assignments in the US and EU. The objective is to examine areas of convergence and divergence in the academic and practical treatment of damages issues in the US and EU. Many of the chapters in the volume are drawn from the papers and discussions generated at the Trans-Atlantic Dialogue meetings of the National Association of Forensic Economics that began in Edinburgh, Scotland, in 2004. That meeting focused on the development of the 'Ogden' multipliers for calculating damages mandated for consideration by UK Courts in 1999. The 2005 meetings (Dublin, Ireland) centred on Markov methodologies used in the US for generating work-life tables and their adoption into damages multipliers, punitive damages, and the process of Irish tort reform. In 2006 discussions in Florence, Italy, focused on methods for calculating non-economic damages in the US and EU as well as the process of harmonization of tort law within the EU. Most recently, the 2007 discussions in Barcelona, Spain, dealt with comparisons of scheduled damages systems in the US and the EU.